Association of composite dietary antioxidant index with cardiovascular disease in adults: results from 2011 to 2020 NHANES - Wang, Run; Tao, Weijun; Cheng, Xiaobing (Frontiers in Cardiovascular Medicine, 2024)
Background Oxidative stress is a known pathogenic mechanism in cardiovascular disease (CVD), yet the association between dietary antioxidants and CVD in the general population remains underexplored. This study leverages data from the National Health and Nutrition Examination Survey (NHANES) to investigate the association of a composite dietary antioxidant index with CVD in US adults. Methods Analyzing data from 25,997 adults (2011–2020 NHANES), we employed weighted generalized linear models, subgroup analysis, threshold effect analyses, and sensitivity analysis to assess the association between dietary antioxidants and CVD. Nonlinear associations were explored through a restricted cubic spline, with gender-specific stratification and threshold effect analysis to identify critical inflection points. Results Increasing levels of the composite dietary antioxidant index corresponded with decreased CVD prevalence (P < 0.001). In all models, weighted generalized linear models revealed a consistent negative association between CVD prevalence. And in Model 3, Quartile 4 had a 29% lower CVD prevalence than Quartile 1[0.71 (0.59, 0.85), P < 0.001]. Meanwhile, the findings of the unweighted logistic regression model demonstrated stability. Various characteristics such as sex, age, race, PIR, education, BMI, alcohol consumption, hypertension, hyperlipidemia, and diabetes did not influence this inverse association (P for interaction >0.05). Notably a nonlinear association was observed, with a significant inflection point at 3.05 among women. Conclusion This study demonstrates a strong negative association between the composite dietary antioxidant index and CVD prevalence, suggesting the potential protective role of dietary antioxidants. These findings underscore the need for prospective studies to further understand the impact of oxidative stress on cardiovascular health.